Enhancement the Life Time of Knife Made of Stainless Steel - Ahmad Fauzi, Muhammad Fikri (IRC, 2018)
Stainless-steels are steel alloy containing high percentage of chromium which makes it a good corrosion resistance alloy. This special property of stainless steel makes it favourable to be used as the material to make kitchen knife. Even though stainless-steel has high corrosion resistance, increasing its hardness is favourable for improvement of the efficiency and time handling of the knife. The development of surface hardening methods makes it possible to achieve a better hardness of the stainless-steel knife. The paper provides analysis of the lifetime of Austenitic stainless- steel knife in terms of hardness and wear resistance after surface hardening process. Nitriding is the surface hardening method used in this study. This report investigated and compared the mechanical properties of the knife after Nitriding process with the untreated stainless-steel knife. The parameter for the Nitriding process of the knife is set to be in pure nitrogen gas atmosphere at elevated temperature of 1150°C for 2 hours of duration. The mechanical properties of the knife are tested on its hardness using Vickers’s Hardness Test. The experiment included optical microscopy, Scanning Electron Microscope and X-Ray Diffraction to provide analysis on the surface of the knife and its microstructure for better understandings of the composition and compound and also to observe the thickness of Nitride layer formed after the surface hardening process.